DETERMINANT FACTORS OF EXCLUSIVE BREASTFEEDING IN KEMUMU OF COMMUNITY HEALTH CENTERS NORTH BENGKULU DISTRICT - Suryanis, Ira; Yanti, Yul (Poltekkes Kemenkes Riau Under Health Ministry Republik Indonesia, 2021)
The World Health Organization (WHO) recommends that Infants should be exclusively breastfeeding for six months to achieve growth, development and health of optimal children. Exclusive breastfeeding is breastfeeding without any fluids or other substances including water except, vitamins, minerals and drugs (WHO, 2018).This study aims to know the determinants of Exclusive Breastfeeding in the Work Area of ​​the Kemumu Health Center in 2020. This type of research is analytical with cross sectional design using quantitative methods. This research was conducted in the Region The work of the Kemumu Health Center in December to February in 2021. A total of 59 samples were taken randomly. Simple Random Sampling with Probability Proportionate method Size which is divided into 1 Kelurahan has 11 Villages, data analyzed using the Chi-Square test (P value = 0.001). The results of this study determined that respondents who gave exclusive breastfeeding were more found in respondents who had positive attitudes compared to respondents who had negative attitudes. The conclusion of this study is that exclusive breastfeeding is also caused by the attitude of the respondents in giving exclusive breastfeeding